2020
DOI: 10.2478/emj-2020-0011
|View full text |Cite
|
Sign up to set email alerts
|

Building production management practice in the construction industry in Nigeria

Abstract: Growing demands for building projects result from economic development. The building industry is dynamic and multifaceted. Efficient and effective practice of building production management (BPM) is required to successfully execute projects and achieve project goals upon completion as well as functionality aims for the lifespan of a building. This research aims to determine factors that influence the BPM practice in the Nigerian construction industry, particularly; during the project execution phase. A cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…[5] also revealed that one way to address these challenges is through an effective building production management practice in the construction industry. [3] describe building production management as the management of building production information, labour, materials, equipment, and other resources to actualize the building project and adhere to building regulations, and contractual conditions project success. Building production management is the primary duty of the building profession [13] [14].…”
Section: Building Production Managementmentioning
confidence: 99%
“…[5] also revealed that one way to address these challenges is through an effective building production management practice in the construction industry. [3] describe building production management as the management of building production information, labour, materials, equipment, and other resources to actualize the building project and adhere to building regulations, and contractual conditions project success. Building production management is the primary duty of the building profession [13] [14].…”
Section: Building Production Managementmentioning
confidence: 99%
“…Fisher and Rajan (1996) "A measure of the expediency with which a building structure can be constructed" optimisation, time optimisation and getting it right at first attempt (Osuizugbo and Ojelabi, 2020;Afolabi and Oyeyipo, 2017). The consideration of buildability must be right from the notional idea proposed by the client (Mydin et al, 2011) and takes into consideration all phases of construction project and facilitates the best use of construction resources (Singhaputtangkul and Low, 2015).…”
Section: Ferguson (1989)mentioning
confidence: 99%
“…This study adopted a field survey method to find out the factors affecting steel structure erection in construction project within Lagos state of Nigeria. The choice for Lagos state was that, the state is the centre of the country's economy, power and commerce and economically significant in Nigeria [15,16]. Secondly, the state has a high number of building construction activities (including steel structures), large concentration of building contractors of various categories and sizes and as well as incessant collapse of buildings in the state [16].…”
Section: Methodsmentioning
confidence: 99%